Elementos estruturais relacionados com a mineralização do eoceno - oligoceno entre Mollebamba e Santo Domingo região de Apurimac, sul do Peru - Huachaca, Hugo Rubén Mamani [UNESP] (2014)
The study area is located in the Central Andes, south of the Abancay deflection, Peru, is inserted in the (Andahuaylas-Yauri) metallogenic province related to this Abancay batholith, which hosts porphyry-type deposits of skarn Fe-(Cu-Au) and load Au Deposits. It is constituted by clastic and carbonate sequences of Mesozoic age, intruded by granodiorite monzonite plutons and stocks that are overlain by oligomiocenic volcanic rocks related with epithermal gold and silver mineralization in the southeastern part of the region. This paper presents a study of the regional geological setting combined with the analysis of structural pattern in the region between Sabaino and Santo Domingo, with the kinematics characterization of five sectors in the area, where mineralization occurs controlled by fault systems. The analysis includes measures of 119 mesoscopic faults with striations, from which was obtained the stress tensor associated with the sin-mineralization stage. Three of the studied sectors (Chama Cocorpiña, Huaychulo) are associated with reverse faults of NNE, while in Santo Domingo sector the mineralized veins are conditioned by normal faults NE, pointing to diverse tectonic processes for the structural control of these deposits. For mineralization in the sectors Chama, Cocorpiña and Huaychulo is assumed the period 40-32 Ma, as they are associated with the second stage intrusion of Abancay batholith. In Mollebamba sector, the mineralization is associated with porphyry Cu-Au (Trapiche Point) whose age corresponds to 29.17 Ma. In the Santo Domingo sector, the auriferous veins are probably contemporary with the veins of the Selene deposit of age 14.62 Ma. The main large structures identified in the area are a NS fold system, which indicates a compressive phase involving shortening approximately EW, and another system represented by two large folds, the Chapi Chapi Anticline and Huillullu Syncline, which have axial planes parallel to the...